IMPLIKASI PENUNJUKKAN LAFAZ MUTHLAQ DAN MUQAYYAD DALAM EPISTIMOLOGI PENETAPAN HUKUM ULAMA MAZHAB - Wardatun Nabilah (Institut Agama Islam Negeri Batusangkar, 2023)
This study wants to examine how the implications of the appointment of lafaz muthlaq and lafaz muqayyad in the determination of law by madhab scholars. This is because the nash of the Quran and hadith were revealed in Arabic, it is necessary to study lafaz to find Allah's message in the establishment of the law. With a qualitative approach in literature research, this study found that there are four implications of using lafaz mutlaq and muqayyad depending on the law and cause of the nash. First, If the object spoken of by the two nashes is the same, and the laws and causes of the nash are the same, then the mutlaq nash is brought to the muqayyad nash. Secondly, if there is a different law and cause, then the mutlaq nash cannot be brought to the muqayyad. Third, if the laws are different but the reasons are the same, then the mutlaq nash cannot be brought to the muqayyad and still practice their respective positions. Fourth, If the laws are the same and the causes are different, then the majority of Hanafiah and Maliki scholars are of the opinion that, nash mutlaq cannot be brought to the muqayyad; while Shafiyya and Hanablah argued that the mutlaq could be brought to the muqayyad